Comparing clinical outcomes between rotator cuff repairs, SLAP repairs, and combined repairs - Lee, Jae H.T. (JSES Int, 2020)
BACKGROUND: Superior labrum lesion from anterior to posterior (SLAP) often presents together with other shoulder pathologies such as rotator cuff tear (RCT), but it is uncertain if repairing both SLAP and RCT has superior clinical outcomes over isolated repairs of SLAP and RCT. MATERIALS AND METHODS: This was a retrospective cohort study with prospectively collected data, reviewing 157 patients who underwent arthroscopic repair of either RCT, SLAP (type II lesion), or both. Before surgery and after 6 weeks, 12 weeks, and 24 weeks, shoulder objective range of motion and strength were measured, patient-reported function and pain was assessed by the modified L’Insalata questionnaire with a Likert scale, and complications after each repair were examined. RESULTS: At 24 weeks after surgery, the combined group (n = 22) and SLAP group (n = 47) had significantly higher forward flexion (165° ± 4° and 167° ± 4° vs. 154° ± 3°, P = .01 and P = .01), external rotation strength (82 ± 6 N, 81 ± 6 N vs. 61 ± 3 N, P = .01 and P = .01), and abduction strength (94 ± 14 N, 78 ± 8 N vs. 53 ± 3 N, P = .001 and P = .02) compared with the rotator cuff tear repair (RCR) group (n = 88). The combined group also had stronger internal rotation than the RCR group (107 ± 12 N vs. 72 ± 4 N, P = .02). Function and pain improved from “severe-moderate” to “moderate-mild” in all groups after surgery. CONCLUSION: Repairing RCT and SLAP tears together results in significant clinical benefits compared to repairing just RCT and analogous results against SLAP-only repair.